Customer satisfaction and its measurement in Islamic banking sector: a revisit and update. Issue 2 (28th November 2018) - Anouze, Abdel Latef M.; Alamro, Ahmed Salameh; Awwad, Abdulkareem Salameh
Abstract : Purpose: The purpose of this study is to answer the following questions: How to measure customer satisfaction from the provisioning service of both: Islamic and Conventional banks? Can we trust one tool to measure such satisfaction or both banks are different identities and there is a need for separate measurement tool? What is the relationship between banks operating style (Islamic or Conventional) and bank performance? Design/methodology/approach: A cross-sectional survey design was conducted to analyze a sample of customers. A total of 480 Jordanian participants were included in the study. Findings: The results of confirmatory factor analysis show that the most important drivers of customer satisfaction are Sharia' compliance, complaints, pricing and convenience, whereas the least important drivers are e-banking, the perception of employees, enjoyment and tangibles. Also, the result of the multi-group analysis shows that the significant impacts of all drivers on customer satisfaction differ from Islamic banks to Conventional banks except for the enjoyment. The significant effects of customer satisfaction on bank performance also differ from Islamic to Conventional banks. Research limitations/implications: The result is limited to the selected sample, and hence, future research in other countries should contribute to a better understanding of the impact of customer satisfaction relationship on bank success or performance. Practical implications: This study provides a useful information for bank managers on the main driver of customer satisfaction and performance. Originality/value: This study is intended to add to the existing literature in three ways: There is a lack of studies on the main drivers of customer satisfaction, especially those based on a consumer's decision-making process in Arabic countries like Jordan. This study broadens the scope by testing the proposed model using data from a sample of consumers in Jordan. This study serves to propose and validate the drivers that influence customer satisfaction and bank performance and elucidate the manner of their influence, to help with the development of more effective business strategies.